(untitled) (Research, Society and Development, 2021)
This study characterizes the allelopathic effect in the germination of Allium cepa seeds, and toxic on the species Artemia salina, of aqueous extracts of leaves of Aspidosperma pyrifolium and Combretum leprosum and the constituent phytochemical compositions. For this, Allium cepa seeds were germinated in systems containing aqueous extracts (200, 400 and 800 mg.L-1) and distilled water, to evaluate aspects of germination, mitotic phases, mitotic index and limit value of cytotoxicity. The toxicity of the aqueous extracts was evaluated in Artemia salina. The extracts were evaluated qualitatively and quantitatively when the substances present to define the phytochemical profile. The aqueous extract of A. pyrifolium negatively affects the germination process in the hypocotyl and seedling growth at 800 mg.L-1. The LC50 found for the aqueous extract of A. pyrifolium was 4986 mg.L-1. The effect of C. leprosum extract on germination resulted in an increase in the dry matter of the root at 400 mg.L-1 and in the density of the dry matter of the root at 800 mg.L-1. In addition, it reduces the seedling matter at 200 mg.L-1, corresponding to the trend observed in the mitotic index, in which this concentration presented a sublethal score for the limit value of cytotoxicity. The maximum concentration evaluated was not sufficient to determine an LC50 in A. salina. The phytochemical profiles of both species demonstrated classes of substances with potential pharmacological application. This information is important because these species are commonly used as food for farm animals and for purposes in folk medicine.